Students’ Character Education Implementation through MABIT (Night of Faith And Piety Development) Program - Rizki Mochamad Soleh; Sri Nurhayati; Prita Kartika (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The study aimed to provide a comprehensive understanding of the implementation and outcomes of the character education program for madrasah students through Mabit activities. This study employs qualitative research methods, using interviews and observations to explore the implementation of character education through Mabit activities at Madrasah Diniyyah Baitul Qur'an Al-Ahad, following a purposive sampling strategy to gather detailed insights from participants. The study found that Mabit (Malam Bina Iman dan Taqwa) activities significantly impact character education in Madrasah Diniyyah. Preparations for Mabit involve socializing with parents and students and preparing learning materials and locations. However, challenges such as inadequate facilities often require renting additional resources. Character development is significantly enhanced through Mabit activities, with students exhibiting increased empathy, discipline, and mutual care. Positive behaviors such as sharing food, avoiding harsh language, and maintaining discipline in worship demonstrate the program's success. Challenges during implementation, such as timing issues and managing large student numbers, are mitigated through logistical support and the supportive environment of the madrasah. The research implies that character education programs like Mabit can be highly effective in religious educational settings if logistical and infrastructural challenges are addressed.